Evaluating audience perception of iconic sound design elements: A Case study on the lightsaber sound from star wars - Barış, Orhun (Graduate School, 2023)
Star Wars is considered to be one of the biggest if not the biggest fantasy franchise in pop culture. The franchise has been mesmerizing the world with its vast universe and its unique atmosphere ever since the release of its first movie Star Wars: A New Hope. Because of that, Star Wars embellished many teenage childhoods such as mine. This appreciation expanded when I grow an interest in sound design since one of the most striking aspects of the movies that helped with the success of the franchise was the exceptional sound design. From the clash of lightsabers to Darth Vader's iconic breathing, many sounds from the original trilogy have become classics starting from 1977 and reaching today. The event that inspired the idea at the core of this research, was born as a result of my personal experience with one of the legendary sounds from Star Wars in an episode of The Mandalorian (2019-), a series show which tells a side story of a bounty hunter. Although it is a side story, it contained most of the iconic sounds and their source objects in the story. It was the sound of a lightsaber in one of the episodes that caught my ear. It felt and sounded different from what I knew as the sound of a lightsaber since my childhood. Then I began to question if other listeners, whether they are die-hard Star Wars fans or not, would react the same way I did. This was the question that inspired the core idea behind the listening experiment which was done in this research that is evaluating the perception of the audience concerning an iconic sound design element. The sound of a lightsaber was selected to examine. It was decided that 2 versions of the sound would be obtained and presented to the audience. For that, the iconic version of the lightsaber sound was extracted from the original trilogy, and the version of the weapons sound from The Mandalorian was selected to compare. The extracted files had to be from scenes that are as synchronous as possible for comparison since the sound of the lightsaber is highly tied to its movement or the action that is being done with the weapon for that matter. At this point, a frequency analysis had to be done to confirm that the versions were in fact different but more importantly, a frequency spectrum analysis had to be done to translate the audible differences between the 2 versions to actual numbers, and findings concerning frequency range and volume. To present the 2 versions to the audience as they are, would be too obvious for a comparison that seeks the perception of an iconic sound. Hence, it was decided a swap of audio between the original and the recent scenes would serve the aim of this research better. Three pairs of videos were created and each video had its audio exchanged with its conjugate with the exception of one pair. The medium for the listening experiment which would present these videos to the audience was chosen to be an online survey because of the ease of sharing it provides and the data representation and analysis tools that the online survey platforms offer. An online survey was constructed in Survey Monkey, and scenes with exchanged audio were presented to the audience together with questions that would help classify the overall participants. The first 4 questions aimed to classify the audience concerning their familiarity and the rest of the survey included 3 comparison question pairs. The pairs are meant to be 2-step comparison phases in which the first question would ask a pure immediate reaction without any guidance or hint concerning the lightsaber, and the second question would ask the participant to specifically comment about the differences that might have heard concerning the sounds of the lightsabers in the presented scenes. The hypothesis going to the establishment and the execution of the survey was, the part of the participants who stated that they are highly familiar with the Star Wars universe was expected to majorly spot the audio swap or comment that what they heard does not feel like it belongs to the image whereas, the participants who think their familiarity was average and below was majorly not expected to spot the audio swap or type a comment which would resemble the notification of the audio exchange. 123 results were gathered between the 6th of November and the 15th of December. The results were as expected for the group which stated average and below familiarity. However, the group which stated high familiarity did not behave as the hypothesis expected. The number of participants from this group that notice the audio exchange was lower than expected, and the number of responses that stated that they did not notice anything at all or the number of responses that commented about the visual components of the scene rather than the audible component, was higher than expected. For this, this research suggested 2 arguments to discuss the unexpected results. The first one suggests the iconic lightsaber sound that one would store in their memory was altered through time and what remains is an imprint that is altered through time and the various Star Wars productions that were made since the original trilogy. The second one was inspired by Michel Chion's (1994) concept of added value and suggested that the togetherness of audio and synchronized video, created a mode of perception that results in the lowered noticeability of the audio swap.
İkonik ses tasarımı öğelerine dair izleyici algısı değerlendirilmesi: Star Wars'tan ışın kılıcı sesi incelemesi
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2023
Keywords: Ses tasarımı; Sound design; Iconic sound design; İkonik ses tasarımı; Star wars